Choosing the Urban Cargo Vehicle - Leite, Cesar Eduardo (European Journal of Applied Sciences, 2021)
The concentration of the population in urban areas and its consequences on the lack of social well-being generate pollution and several inconveniences for this population. The Urban Cargo Transport service - UCT, which has one of its bottlenecks in the Urban Cargo Vehicle – UCV, is seen as one of the main generators of these inconveniences. This work seeks to identify gaps in the research carried out on the UCT, aimed at choosing the UCV that offers less impact on inconveniences. With the Systematic Literature Review – SLR, articles are selected, which are studied in-depth and demonstrate the trends presented here.